Corporate entrepreneurship in the public sector: a South African perspective - Malatjie, I.; Garg, A.; Rankhumise, E. (International Conference on Public Administration and Development Alternatives (IPADA), 2017)
Over the last three decades, organisations worldwide have used corporate entrepreneurship (CE) as a means of building new competencies, revitalizing operations, achieving renewal, and creating value for stakeholders. However, little is understood about factors triggering CE within the public sector. The aim of this paper was to collect relevant principles and concepts from existing entrepreneurship and CE literature, which could then be refined, developed and used in the public sector to foster a new entrepreneurial-orientated climate. This paper determines the entrepreneurial orientation (EO) amongst managers and what antecedents promote entrepreneurship in the public sector. It used data from managers within organisations under the Minister of Public Service and Administration (MPSA). The findings of this study can therefore be used to develop strategies that can be applied within the public sector as a whole to improve organisational performance. This paper concludes with a discussion on implications for both theory and practise.
Journal article, Published in International Conference on Public Administration and Development Alternatives (IPADA), The 2nd Annual Conference on ‛‛ The Independence of African States in the Age of Globalisation”, July 26-28, 2017,
Keywords: Corporate entrepreneurship; Entrepreneurial orientation; Social entrepreneurship; Entrepreneurship -- South Africa; Social entrepreneurship; Public administration -- South Africa